Triaxial accelerometer calibration using an extended two-step methodology - Menezes Filho, Rogério; Silva, Felipe; Carvalho, Gustavo; Vieira, Leonardo (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2020: Anais do XII Simpósio Brasileiro de Robótica e XVII Simpósio Latino Americano de Robótica, 2020)
Accelerometers are versatile devices employed in a variety of areas. However, depending on the application, requirements for accuracy and reliability vary substantially. For instance, stand-alone inertial navigation requires high quality sensors, while integrated navigation can be implemented using inferior but less costly accelerometers, especially MEMSs (Microeletromechanical Systems). Nevertheless, such sensors can often have the performance improved by a procedure known as calibration, which estimates and compensate for their systematic errors. As main contribution of this study, we adapt and implement a calibration methodology originally designed for magnetometers in a consumer-grade, MEMS, triaxial accelerometer. The technique, called extended two-step, is based on a pseudo least squares estimation, and is suitable for in-field implementation. Since it is both simple and efficient, it is worth using the methodology for accelerometers as well. This is only possible because, instead of using the Earth’s local magnetic field vector, local gravity is employed as reference. In this version, the sensor must be rotated to multiple orientations and kept static, while data is acquired. Biases, scale factors and the nonorthogonalities between the sensors’ axes are estimated. Calibration with simulated and real data is conducted in order to validate the adaptation.